Analisis Unsur Kerugian Keuangan Negara dalam Perkara Pembiayaan Kredit Usaha Rakyat Sistem Bayar Panen : Studi Kasus Putusan Nomor 41/Pid.Sus.TPK/2024/PN. MTR - Roli Pebrianto; Noviana Noviana; Muhammad Panji Prabu Dharma; Syarif Dahlan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study seeks to examine how the element of state financial loss is applied in corruption cases that originate from private-law relationships, specifically in the context of Micro People’s Business Credit (KUR) financing using the Yarnen Porang scheme, as reflected in Decision Number 41/Pid.Sus.TPK/PN.MTR. The central issue addressed is the manner in which the panel of judges construed and affirmed the existence of a state financial loss that, in substance, arose from a civil act, namely the performance of a financing cooperation agreement between a banking institution and an offtaker. By employing a normative juridical approach and conducting an in-depth analysis of the judicial decision, this research concludes that the alleged state financial loss in the a quo case remains merely prospective in nature and does not satisfy the requirement of an actual and definite loss as mandated by positive law. Furthermore, evidence demonstrating that the financing funds were enjoyed by a third party rather than by the accused indicates a misapplication in attributing criminal liability. Consequently, the criminal prosecution of conduct that is essentially civil in character reflects an expansive interpretation of the state loss element, which is inconsistent with the principle of legality and the doctrine of prudence in the enforcement of corruption laws.